If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + 9 = 73 + y Reorder the terms: 9 + 8y = 73 + y Solving 9 + 8y = 73 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 9 + 8y + -1y = 73 + y + -1y Combine like terms: 8y + -1y = 7y 9 + 7y = 73 + y + -1y Combine like terms: y + -1y = 0 9 + 7y = 73 + 0 9 + 7y = 73 Add '-9' to each side of the equation. 9 + -9 + 7y = 73 + -9 Combine like terms: 9 + -9 = 0 0 + 7y = 73 + -9 7y = 73 + -9 Combine like terms: 73 + -9 = 64 7y = 64 Divide each side by '7'. y = 9.142857143 Simplifying y = 9.142857143
| 13n+11=5n+219 | | 24-(14x-8)-(3+12x)=4-(8x+11) | | 5a+2=17a-5 | | 3v=0.6 | | 3/4z=1/4z+12 | | n^3/2=729 | | -4y=20+4 | | (4k+3)(3k-5)= | | x/2-x/3=5 | | n+x+27=7 | | 1=5k-6k | | x^2-8xb+15b+1=0 | | 8=-5-6m-5 | | 4x+7+3x+5=2x+2 | | 5n+6=3(2n+10) | | 8-10x=93-45x | | 4w+19=149 | | 6(-3.2941)-4y=-24 | | 6*x+6*x+3=48 | | -5z+23=126 | | 6x+10x=78+x | | 3k^2+k-10=0 | | c=0.7y+50 | | -7y-16=16 | | 6x-4(2/7x+2)=-24 | | 3x-(7x-5)=1 | | 3(3+3r)+1=37 | | (3/8)^2/(3/7+3/14) | | (3/8)^2/(3/7+3/13) | | 6x^2-9x= | | 2y+23+90=180 | | a+6-6=5 |